2020
DOI: 10.1002/xrs.3139
|View full text |Cite
|
Sign up to set email alerts
|

Portable X‐ray fluorescence device reveals the artistic palette of Carlo Bononi, Baroque artist from Ferrara

Abstract: The principal aim of the in situ X-ray fluorescence (XRF) analysis on the canvas "The Coronation of the Virgin" was to characterise the colour palette of Carlo Bononi (Ferrara, 1580-1632), a lesser-known artist of the early Baroque period in Ferrara. More than 100 points were collected by means of an XRF spectrometer, but the presence of many overlapping painted layers left some doubts about the preparation and the background layers. The scanning electron microscopy with energy dispersive spectrometer analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…For example, there already exist several papers that lack type characterisation (for various reasons) and whose dating falls within/outside the indicated chronological range. These latter studies reported the presence of lead-tin yellow pigments on artworks dated from the 6 th (Hedegaard et al 2019) to the 16 th (Spring 2007;Espejo Arias et al 2008;Križnar et al 2009;Amadori et al 2013;Franquelo et al 2015;Aurélie et al 2016;Martin-Ramos et al 2017;Doménech-Carbó et al 2019;Impallaria et al 2020), 17 th (Križnar et al 2019;Uhlir et al 2019;Delaney et al 2020) and 18 th (Cortea et al 2020) centuries. Indeed, more extensive and detailed studies are required, in order to draw an indisputable chronological picture of the use of these pigments.…”
Section: Lead-tin Yellow Type IImentioning
confidence: 96%
“…For example, there already exist several papers that lack type characterisation (for various reasons) and whose dating falls within/outside the indicated chronological range. These latter studies reported the presence of lead-tin yellow pigments on artworks dated from the 6 th (Hedegaard et al 2019) to the 16 th (Spring 2007;Espejo Arias et al 2008;Križnar et al 2009;Amadori et al 2013;Franquelo et al 2015;Aurélie et al 2016;Martin-Ramos et al 2017;Doménech-Carbó et al 2019;Impallaria et al 2020), 17 th (Križnar et al 2019;Uhlir et al 2019;Delaney et al 2020) and 18 th (Cortea et al 2020) centuries. Indeed, more extensive and detailed studies are required, in order to draw an indisputable chronological picture of the use of these pigments.…”
Section: Lead-tin Yellow Type IImentioning
confidence: 96%
“…11 When investigating pigments in historical paintings, the analysis might reasonably be limited to MA-XRF as key pigments used until the end of the 19th century are mainly inorganic. 12 Consequently, a particular MA-XRF elemental map is probably showing the distribution of the pigment(s) associated with it. 13 This was utilized for example, to assist a conservation treatment of a 15th century panel painting 14 ; to solve ambiguities of a painting by the Italian Renaissance Master Raphael.…”
Section: Introductionmentioning
confidence: 99%
“…When investigating pigments in historical paintings, the analysis might reasonably be limited to MA‐XRF as key pigments used until the end of the 19th century are mainly inorganic 12 . Consequently, a particular MA‐XRF elemental map is probably showing the distribution of the pigment(s) associated with it 13 .…”
Section: Introductionmentioning
confidence: 99%